The role of IL-6, IL-10, and PGE2 in the treatment of intervertebral disc herniation by dual-channel endoscopic lumbar discectomy - Du, Peijin; Zhang, Qingshan; Zhang, Yaning (Cellular and Molecular Biology, 2022)
is the This study aimed to explore the role of IL-6, IL-10, and PGE2 in the treatment of intervertebral disc herniation with dual-channel endoscopic lumbar discectomy. For this purpose, we selected 182 patients with intervertebral disc herniation in our hospital and randomly divided them into the control group and the study group according to the order of admission, of which 85 cases were in the control group, 97 cases in the study group, and control group was treated with conventional lumbar discectomy; the study group was treated with dual-channel spine endoscopic lumbar discectomy to observe and compare the operation-related indexes, lumbar function indexes, clinical effects, serum-related indexes and the evaluation value of the two groups of patients. Results showed that the operation time, incision length, intraoperative blood loss, hospital stay, and postoperative pain scores of the study group were lower than those of the control group (p<0.05); the ODI and RMQ scores of the study group after treatment were lower than those of the control group (P<0.05). The excellent and good rate of the study group was 89.69% higher than that of the control group 77.65% (p<0.05); the levels of IL-6 and PGE2 in the study group after treatment were lower than those of the control group, and the IL-10 level was higher than that of the control group. (P<0.05); Using the lumbar spine function score as the comparison standard: IL-6, IL-10, PGE2 for the evaluation value of dual-channel endoscopic lumbar discectomy for the treatment of intervertebral disc herniation: sensitivity 96.18%, specificity 96.27%, the accuracy of 97.06% was higher than the single diagnosis result (P<0.05. It is worthy of clinical promotion. IL-6, IL-10, PGE2 predict dual-channel spine Endoscopic lumbar discectomy for the treatment of intervertebral disc herniation has high prognostic sensitivity and accuracy, which can provide references for clinical treatment and prognostic medication.